2010
DOI: 10.4097/kjae.2010.58.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Inter-arm arterial pressure difference caused by prone position in the thoracic outlet syndrome patient -A case report-

Abstract: Thoracic outlet syndrome has neurologic symptoms caused by compression of brachial plexus, blood vessel symptoms are caused by compression of the artery or vein. The authors report a case of sudden decrease in blood pressure of the left arm after turning the patient from supine position to prone position. They confirmed that the patient had thoracic outlet syndrome after performing computed tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…[7,[23][24][25][26][27] Various pathological causes have been considered as leading to an increase in interarm BP differences such as atherosclerosis, vasculitis, fibromuscular hyperplasia, connective tissue, and thoracic outlet compression. [10][11][12][13][14][15] In the absence of anatomic obstruction, interarm differences in SBP were thought to be related to some intrinsic property of the cardiovascular system. Studies by Canepa et al showed that interarm difference in SBP was based on alterations in arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,[23][24][25][26][27] Various pathological causes have been considered as leading to an increase in interarm BP differences such as atherosclerosis, vasculitis, fibromuscular hyperplasia, connective tissue, and thoracic outlet compression. [10][11][12][13][14][15] In the absence of anatomic obstruction, interarm differences in SBP were thought to be related to some intrinsic property of the cardiovascular system. Studies by Canepa et al showed that interarm difference in SBP was based on alterations in arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Fibromuscular dysplasia and vessel compression can cause limb ischemia even though they do not have an atherosclerotic process. [14,15] All the above studies emphasize the significance of recognizing baseline IAD so that hypertension, as well as other disease processes, can be detected earlier and hence managed more effectively. Although prevalence and magnitude of IAD among Western population is available, little is known regarding the magnitude and prevalence of IAD in Indian population.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, blood pressure was measured in a supine position in group C, and in a sitting position in groups A and B. Although there was no difference between supine and sitting IASBPD ( n = 30; data not shown), postural difference could have affected the present results, as IASBPD measured in a supine and sitting position might differ …”
Section: Discussionmentioning
confidence: 55%
“…Although there was no difference between supine and sitting IASBPD (n = 30; data not shown), postural difference could have affected the present results, as IASBPD measured in a supine and sitting position might differ. 29 The present study had several limitations. First, the number of participants included was not enough to enable definite conclusions to be reached.…”
Section: Discussionmentioning
confidence: 82%
“…A previous study suggested that the cause of |ΔSBP| ≥10 mm Hg was pathologic rather than physiologic [17]. In addition to anatomical evidence for |ΔSBP| ≥10 mm Hg, aortic dissections, aortitis, infraclavicular arterial occlusion, and arterial embolism may be attributed to a thrombus complicated by atrial fibrillation, congenital coarctation of the aorta, or higher BP in the left arm, compared with the right arm [18] [19]. In this study, the percentage of patients with |ΔSBP| ≥10 mm Hg (6.0%) was similar to that found in previous studies.…”
Section: Causes Of |δSbp| ≥10 MM Hg and Sample Size Calculated As Thmentioning
confidence: 99%